Endolithic microbial diversity in sandstone and granite from the McMurdo Dry Valleys, Antarctica - Archer, Stephen D. J.; Ríos, Asunción de los; Lee, Kevin C.; Niederberger, Thomas S.; Cary, S. Craig; Coyne, Kathryn J.; Douglas, Susanne; Lacap-Bugler, Donnabella C.; Pointing, Stephen B. (Polar Biology, 2017)
Cryptic microbial communities develop within rocky substrates in Antarctica’s McMurdo Dry Valleys as a stress avoidance strategy. They may be cryptoendolithic within pore spaces of weathered rocks, or develop in cracks and fissures as chasmoendolithic communities and are characterised by coloured bands of colonisation. Here we used a precision drill to recover fractions from black, white, green and red layers within colonised granite and sandstone. We combined backscattered scanning electron microscopy and high-throughput sequencing to identify major taxa in each band. We confirmed the presence of algal and fungal lichen symbionts, cyanobacteria and free-living algae, plus a diverse heterotrophic bacterial and archaeal component. A clear delineation at the community level was observed. The relatively biodiverse and heterogenous lichen communities occurred in weathered sandstone cliffs, whilst in granite and sandstone boulders, cyanobacterial communities were dominant. Differences between coloured bands of colonisation within each community were less clear. The study demonstrates that endolithic microbial communities can be recovered using a drill technology similar to that planned for the search for endolithic biosignatures on Mars. Research was supported financially by Dr de los Ríos (CTM2012-38222-C02-02 from the MINECO and PRX15/00478 Salvador Madariaga from the MEC, Spain). Peer Reviewed